Operationalization of One Health Burnout Prevention and Recovery: Participatory Action Research-Design of Nature-Based Health Promotion Interventions for Employees - Sterckx, Ann; Van den Broeck, Kris; Remmen, Roy; Dekeirel, Kathleen; Hermans, Hildegard; Hesters, Carmen; Daeseleire, Tine; Broes, Viki; Barton, Jo; Gladwell, Valerie; Dandy, Sarah; Connors, Michéal; et al. (Frontiers in Public Health, 2021)
Burnout is, besides a global, complex phenomenon, a public health issue with negative consequences on personal, organizational, social, and economic levels. This paper outlines the co-design of a novel Nature-based Burnout Coaching intervention, called NABUCO. Due to the complexity of burnout, we propose a One Health approach in healthcare, educational and governmental pilot organizations, to deliver guidelines and protocols for prevention and recovery of burnout. We advocate the inclusion of the salutogenic and mutual healing capacity of nature connectedness, facilitating a positive impact on mental and environmental health. A transdisciplinary Participative Action Research-design resulted in an iterative adaptive cycle of co-design, implementation, and evaluation of NABUCO.